Development of Contextual Math-Edutainment: The Interactive "Geomath" Game to Enhance Seventh-Grade Junior High School Students’ Understanding of Geometry - Pramesti, Santika Lya Diah; Salsabila, Nindya Ayu (JDIME: Journal of Development and Innovation in Mathematics Education, 2024)
This study aims to develop and evaluate a contextual game-based learning media called Geomaster, designed to enhance seventh-grade students' understanding of geometry concepts. Employing the ADDIE development model, the research followed systematic stages including analysis, design, development, implementation, and evaluation. The product was validated by six experts—three media experts and three subject matter experts—yielding an average feasibility rating of 91% and 95% respectively, indicating that the media was highly feasible for use. The trial phase was conducted in three stages: small-scale, large-scale, and implementation trials. Results from small-scale trials demonstrated positive feedback from both students (93%) and teachers (91.3%) regarding media readability, clarity, and motivational impact. In large-scale trials, student responses averaged 89.8%, and teacher responses averaged 90.25%, reinforcing the media’s effectiveness. Furthermore, implementation trials indicated that the media supported various student learning activities with an average rating of 80.3% and achieved a high N-gain score of 0.72, reflecting significant improvement in learning outcomes. The study concludes that Geomaster effectively enhances conceptual understanding, fosters engagement, and supports the integration of interactive digital media in geometry instruction. This research contributes to the growing body of literature advocating for gamification in mathematics education and highlights the importance of developing innovative learning media to meet the demands of 21st-century learners.